THE IMPACT OF INTERNATIONALIZATION ON MANAGEMENT CONTROL SYSTEMS BUSINESS OF THE BRAZILIAN TEXTILE INDUSTRY: CASE STUDIES OF WOMEN'S FASHION SEGMENT - Lopes, Raphael de Souza Sant'Anna (2013)
International borders have become increasingly smaller with globalization, and companies increasingly comes surpassing these limits in order to obtain new business opportunities. Thus, the management control systems undergo changes for companies to meet the needs of the global economy. The objective of this research is: reporting the characteristics of managerial control in internationalized companies, and ascertain whether the internationalization generated impact on control systems. The target segment of this study is the textile segment womenswear. This is a descriptive and qualitative, through a multiple case study, with seven companies in this segment. For data collection, we used a questionnaire with open and closed questions. Subsequently, through analysis, the data were compared to literature. The results show that the adaptation of control systems to the process of internationalization has not occurred on large levels. Evidence also suggests that management control systems and the process of internationalization of the companies surveyed, with some exceptions, are consistent with the literature used in this research.